Sex determination from femora in late antique sample from Eastern Adriatic coast (Salona necropolis) - Jerković, Ivan; Bašić, Željana; Kružić, Ivana; Anđelinović, Šimun (Anthropological Review, 2016)
The determination of sex is one of the first steps in anthropological analysis. When skeletal remains are fragmented, the most useful approach is application of osteometric methods. The methods are population specific, and therefore require development of discriminant functions for each population group. The aim of this study was to test sexual dimorphism of femoral measurements and to calculate discriminant functions applicable for sex determination on fragmented skeletal remains on the late antique sample from the Eastern Adriatic coast (2nd–6th century AD). 214 randomly chosen skeletons from the excavation site Solin-Smiljanovac were analyzed. Sex and age were assessed using standard anthropological methods, and skeletons were examined for pathologic and traumatic changes. In the next step, we selected 27 female and 48 male skeletons free of peri- or post-mortem changes that could affect measurements Eight standard femoral measurements were taken. Sexual dimorphism was initially compared using independent sample t test, after which discriminant functions were computed. All femoral measurements showed statistically significant sexual dimorphism (p<0.001). Ten discriminant functions for every part of femur were calculated and obtained classification accuracy of 73.1–91.8%. This study reached relatively high classification, which will improve further analysis of the skeletal remainsn from the Salona necropolis. Due to similar population structure in the Roman period across the Adriatic coast, the discriminant functions could be applicable for all populations from the same period and area. This study also raised a few methodological questions showing that when creating discriminant functions we should consider not only the accuracy, but also the applicability based on the experience from the anthropology laboratory that considers the state of preservation and frequent pathology.